2019
DOI: 10.1186/s12864-019-6368-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen cyanamide induces grape bud endodormancy release through carbohydrate metabolism and plant hormone signaling

Abstract: BackgroundGrape buds exhibit non-uniform, or delayed, break in early spring in subtropical regions because the accumulation of chilling is insufficient. Hydrogen cyanamide (H2CN2, HC) can partially replace chilling to effectively promote bud sprouting and is used widely in warm winter areas. However, the exact underlying mechanism of grape bud release from endodormancy induced by HC remains elusive.ResultsIn this study, the transcriptome of grape winter buds under in vitro conditions following HC and water tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 36 publications
(54 reference statements)
4
39
0
1
Order By: Relevance
“…Interestingly, Kuroda et al, 2005 found that an exogenous application of H 2 O 2 (2.5%) to the endodormant buds of Japanese pear increased bud break, but it required a higher concentration of H 2 O 2 (10%) to attain a similar bud break rate when the application was made during ecodormancy. Treatments with hydrogen cyanamide (HC), a dormancy-breaking agent, were also found to substitute chilling requirements in grapevine and Japanese pear by inducing H 2 O 2 accumulation in the buds ( Kuroda and Sugiura, 2002 ; Liang et al, 2019 ). In both species, the accumulation profile of H 2 O 2 during endodormancy was similar to what we observed in the present study ( Figure 2B ), where H 2 O 2 reaches its peak at endodormancy release and declines during ecodormancy ( Kuroda and Sugiura, 2002 ; Pérez et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Kuroda et al, 2005 found that an exogenous application of H 2 O 2 (2.5%) to the endodormant buds of Japanese pear increased bud break, but it required a higher concentration of H 2 O 2 (10%) to attain a similar bud break rate when the application was made during ecodormancy. Treatments with hydrogen cyanamide (HC), a dormancy-breaking agent, were also found to substitute chilling requirements in grapevine and Japanese pear by inducing H 2 O 2 accumulation in the buds ( Kuroda and Sugiura, 2002 ; Liang et al, 2019 ). In both species, the accumulation profile of H 2 O 2 during endodormancy was similar to what we observed in the present study ( Figure 2B ), where H 2 O 2 reaches its peak at endodormancy release and declines during ecodormancy ( Kuroda and Sugiura, 2002 ; Pérez et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in barley seeds, NADPH oxidase induces ABA catabolism and α-amylase activity, which are prerequisite for seed germination [35]. Along the same vein, exogenous application of HC which is widely reported to induce H 2 O 2 production, decreases endogenous ABA levels in grape [45,46] and sweet cherry [47] by promoting ABA degradation and inhibiting ABA synthesis. In walnut, redox interaction rather than sugar metabolism was found to govern bud dormancy release [18].…”
Section: Introductionmentioning
confidence: 96%
“…In addition, through the catalysis of nucleotide-diphospho-sugar (NDP-sugar) interconversion enzymes (NSEs), many other NDP sugars were produced from UDP-Glc and GDP-Man 28 . Another way is that sucrose invertase (INV) and hexokinase (HK) catalyze the production of D-Glucose-6P from sucrose 29 . Subsequently, D-Glucose-6P is converted into UDP-Gal, UDP-GalA, UDP-Rha and other polysaccharide precursors under the catalysis of enzymes such as Phosphoglucomutase (PGM), UTP-glucose-1-phosphate Uridylyltransferase (UGP2), and UDP-apiose/xylose synthase (AXS) et al 30 .…”
Section: Introductionmentioning
confidence: 99%